Development of a telepharmacy service for patients receiving antiretroviral medication through postal medicine delivery at Nakornping Hospital, Chiang Mai - Yingyong, Pacharaporn; Kornjirakasemsan , Akarawat; Paengtrai , Sobhon (Journal of Nakornping Hospital, 2025)
Introduction: In 2022, patients receiving antiretroviral medications via postal delivery at Nakornping Hospital lacked continuous pharmaceutical care, which may lead to medication-related problems. This study aimed to develop a telepharmacy service system for this patient group. Objective: To develop a telepharmacy service for patients receiving antiretroviral medication via postal medicine delivery and compare clinical outcomes, medication adherence, drug-related problems, and patient satisfaction with those receiving care at the outpatient department. Method: This action research was conducted from February to September 2023 using the Plan–Act–Observe–Reflect (PAOR) cycle in four phases: 1) situation analysis, 2) system development, 3) implementation, and 4) evaluation. The intervention group included 98 stable PLHIV receiving ART by post. The control group included 97 patients receiving pharmaceutical care at the OPD. Data were analyzed using descriptive statistics and inferential statistics, including Fisher’s exact test, Independent t-test, Rank sum test, and Mixed-effect model. Results: The developed telepharmacy system consisted of four main components: 1) patient identity verification, 2) pharmaceutical consultation via Speedy Tele and Line application to improve service accessibility, 3) documentation in the electronic medical record (EMR) to ensure accurate and continuous access to medication and treatment information, and 4) integration with the hospital information system (HIS) to support multidisciplinary care planning. After implementation, comparison results showed no statistically significant differences between the intervention and control groups in CD4 count, viral load, or opportunistic infections. No new or recurrent opportunistic infections were found in either group. Medication adherence improved significantly in both groups (p < 0.001). The intervention group reported the highest satisfaction level (4.92 ± 0.26), compared to the control group (4.03 ± 1.12). If patients in the intervention group had to travel to the hospital, the median travel cost would be 275 THB and the median travel time would be 60 minutes. Conclusion: The telepharmacy service system enables pharmacists to effectively manage and support patients with HIV and stable AIDS conditions without compromising clinical outcomes. Additionally, it enhances patient satisfaction while reducing both financial and time burdens associated with hospital visits.